Structure of Fukui matrices - Bochicchio, Roberto Carlos (2017)
Fukui matrices considered as the generalization of the concept of Fukui densities are decomposed into their pairing and unpairing contributions within the theory of the reduced density matrices. Their algebraic structure become clear from this decomposition providing their relationships with the spin density matrices and the irreducible part of the second-order reduced density matrix cumulant, that is, the explicit contributions of the many-body or correlation effects. The uncorrelated state function approximation is a simple way to emphasize the physical meaning of these matrices and represents the appropriate starting point for the treatment of a quasi-analytical model to denote the occurrence of correlation effects.